Synthesis and reactivity of platinum(II) cis-dialkyl, cis-alkyl chloro, and cis-alkyl hydrido bis-N-heterocyclic carbene chelate complexes - Brendel, Matthias; Engelke, René; Desai, Vidya; Rominger, Frank; Hofmann, Peter (Organometallics, 2015)
Platinum(II) cis-dimethyl and cis-dineopentyl complexes bearing the alkyl-substituted bis-NHC ligands Lt-Bu, LMe, and Li-Pr (Lt-Bu = 1,1′-di-tert-butyl-3,3′-methylenediimidazolin-2,2′-diylidene, LMe = 1,1′-dimethyl-3,3′-methylenediimidazolin-2,2′-diylidene, Li-Pr = 1,1′-diisopropyl-3,3′-methylenediimidazolin-2,2′-diylidene) as well as novel cis-alkyl chloro and cis-alkyl hydrido compounds were synthesized. The reactivity of the dimethyl complexes toward dichloromethane and methanol was investigated. Reductive elimination of alkanes from cis-alkyl hydrido complexes requires much higher temperatures than in related bisphosphine systems, which limits their applicability for the generation of reactive, bent platinum(0) d10-ML2 fragments for bond-activation chemistry. The platinum(II) complexes were characterized by NMR and IR spectroscopy, mass spectrometry, elemental analysis, and X-ray diffraction in most cases.